Fabrication and characterization of silicon based vertical electrode Nanogap biosensor for protein detection - Norbi Hayati Mohd Noor (School of Microelectronic Engineering, 2010)
The main objective of this research is to design, fabricate, characterize, and test the silicon based vertical electrode Nanogap biosensor which will be used to detect and identify target proteins in aqueous solution.